Liberation Theology: A Comparative Study of Christian and Islamic Approaches - Ciftci, Mehmet (New blackfriars, 2015)
Research into liberation theologies has rarely had an interreligious perspective. To that end, I shall carry out a comparative study of Christian and Islamic versions of liberation theology and I shall highlight the similarities and differences in their approaches. It will be a thematic study that is structured around three key mentalities which are shared by the approaches of both religious traditions. Firstly, the need to reinterpret their own religions from the perspective of the poor; secondly the interrelated emphases on action, orthopraxy and the agency of the oppressed; and thirdly a rejection of excessive other-worldliness. I conclude from my analyses with the following hypotheses: firstly, due to the lack of an authority akin to the Catholic Church, Islamic liberation theology is comparatively more likely to create the potential for social upheaval and is more likely to lead to an attenuation of metaphysical religious feeling; secondly, all liberation theologies contain latently the potential for creating millenarian outbursts; the best example to offer from modern history of this latent feature becoming manifest is in the Iranian Islamic revolution of 1979.